1998
DOI: 10.1111/j.1442-9071.1998.tb01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive intra‐operative local anaesthesia in paediatric strabismus surgery: A randomized controlled trial

Abstract: Neither topical amethocaine nor subconjunctival bupivacaine makes a clinically significant difference to postoperative pain, emesis or length of stay. Moderate dose paracetamol per rectum alone appears to be effective analgesia for strabismus surgery, although it probably masked any small adjunctive effect of the topical anaesthesia used in the present trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
1
6
1
1
Order By: Relevance
“…10 Topical amethocaine 1% drops and subconjunctival infiltration with bupivacaine 0.5% administered at the conclusion of strabismus surgery have been shown to be equally effective in reducing postoperative pain, [11][12][13] although another study did not show any additional analgesic effect of either of these interventions when compared to placebo. 14 Our pilot study found that a subtenons injection of lidocaine was associated with a reduction in postoperative systemic analgesia requirement (29% vs. 64% of controls, P ϭ 0.052), and with a trend to reduced pain scores that reached statistical significance at the 2-h observation. 1 The full-scale trial did not confirm the pilot study's finding of a reduction in systemic analgesia requirement in patients receiving subtenons lidocaine.…”
Section: Discussionmentioning
confidence: 91%
“…10 Topical amethocaine 1% drops and subconjunctival infiltration with bupivacaine 0.5% administered at the conclusion of strabismus surgery have been shown to be equally effective in reducing postoperative pain, [11][12][13] although another study did not show any additional analgesic effect of either of these interventions when compared to placebo. 14 Our pilot study found that a subtenons injection of lidocaine was associated with a reduction in postoperative systemic analgesia requirement (29% vs. 64% of controls, P ϭ 0.052), and with a trend to reduced pain scores that reached statistical significance at the 2-h observation. 1 The full-scale trial did not confirm the pilot study's finding of a reduction in systemic analgesia requirement in patients receiving subtenons lidocaine.…”
Section: Discussionmentioning
confidence: 91%
“…Nausea and vomiting are also common after squint surgery, occurring in 18% to 54% of patients 11 12. Postoperative pain appears to be a clear predictor of nausea and vomiting in children 4.…”
mentioning
confidence: 99%
“…48,49 There is evidence of an association between topical diclofenac 50 and excellent analgesia with a low incidence of PONV; however, this benefit has not been demonstrated with ketorolac. 49 …”
Section: Opioidsmentioning
confidence: 99%
“…7,26 Analgésiques topiques L'efficacité de la tétracaïne topique a été démontrée dans deux études séparées; 46,47 toutefois, deux autres études n'ont pas montré d'avantage. 48,49 Certaines données soutiennent une association entre le diclofénac topique 50 et une excellente analgésie accompagnée d'une faible incidence de NVPO, mais cet avantage n'a pas été démontré avec le kétorolac. 49 …”
Section: Opioïdesunclassified